2021
DOI: 10.4018/ijvple.2021070101
|View full text |Cite
|
Sign up to set email alerts
|

ESL Learning via Facebook Among Science and Non-Science University Students

Abstract: This study examines science and non-science students' perceptions of the effects of Facebook on their ESL learning. A questionnaire was used to gather data from 631 university students in Malaysia. The findings suggest the science students' more positive views of Facebook for ESL learning compared to their non-Science counterparts, although the differences in percentages between the two groups are small. The science students perceived higher confidence and motivation to read, speak, and write in English, in on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…The finding supports Kasuma and Tan (2019) 's research on university students' text preference in an online task. According to the study, the students were more interested in non-academic texts, especially creative texts such as short stories and extracts from popular novels and poems.…”
Section: Discussionsupporting
confidence: 87%
“…The finding supports Kasuma and Tan (2019) 's research on university students' text preference in an online task. According to the study, the students were more interested in non-academic texts, especially creative texts such as short stories and extracts from popular novels and poems.…”
Section: Discussionsupporting
confidence: 87%
“…Apart from that, in terms of reading, students are able to acquire vocabulary and learn sentence structures when the lessons were delivered in Facebook. It helps students become more comfortable reading content in the English language by introducing them to new phrases and sentence construction (Kasuma & Tan, 2019). Therefore, it can be said that social media has become an essential tool to be used in order to deliver the impactful ESL lessons from the ESL educators.…”
Section: Social Media Platforms In Esl Classroommentioning
confidence: 99%
“…They also argued that the structure of learning materials posted through the Telegram had a positive effect on how the learners perceived the learning environment and participated in the learning process. In ESL context, Kasuma (2021) found that incorporating Facebook, as a social media, facilitated the use of preferred learning styles and strategies, which enhanced learners’ learning interest, improved their language abilities, and provided them with the best academic experience. Nugroho and Atmojo (2020) explored EFL learners’ insights and instructional activities of digital learning of English in a flipped classroom.…”
Section: Literature Reviewmentioning
confidence: 99%